''You have your eyesight and you do not see:" Representations of sight and blindness as manifested in the artistic and verbal expressions of adults who grew up in the shadow of a secret. (September 2022) - Sela, Tal; Bat-Or, Michal
Abstract: This study explored the explicit and implicit subjective experiences of 11 adults who grew up in the shadow of a secret. A first attempt to combine art-based research methods with qualitative research on this topic, this study used the phenomenological approach and categorical content analysis to identify recurring verbal and non-verbal themes, as they emerged from three different mediums: readymade art, a story based on the visual artwork, and semi-structured interviews with participants. Participants also utilized intermodal transfer, a transition from one art form to another, which made focusing on various aspects of the phenomenon possible. Representations of sight and blindness were predominant in the three mediums. Aspects of visibility versus concealment also emerged, as well as representations of childhood as a multi-layered, obscure or vague reality where things are not as they appear at first sight. The discussion deals with metaphors of sight and blindness as reflected in the three mediums as well as how these three mediums enrich and deepen our understanding of these themes. It also examines possible applications of this research in the field of psychotherapy, study limitations and suggestions for future research. Highlights: A qualitative analysis of the experience of growing up in the shadow of a secret. Use of intermodal transfer and interviews produced explicit and implicit knowledge. Themes of sight and blindness arose with all participants.